The Influence of Anime on Gen Z's Behavior and Social Interactions - Cut Yasmin Zafira; Setiawati, Rieke; Zahrani, Regina Frida; Paramita, Allicia Galuh; Hendriyan, Amanda Pricillia; Farida, Rima Tria; Abdurrahman, Hasan; Lestari, Humannisa Rubina (Journal of Social Interactions and Humanities, 2024)
Popular Japanese animation, or anime, has impacted many facets of culture and society, especially among Indonesia's Gen Z young people. In order to comprehend how imitation and digital literacy enable Gen Z to absorb anime culture and its effects on social norms and behavioral patterns, the research employs psychological and sociological methods. The study draws attention to Gen Z's growing interest in Japanese culture, which may have an effect on Indonesian social norms. Fandoms are also fostered by anime, and they show their devotion through cosplay and online discussion boards. The purpose of the study is to comprehend the social factors that influence Gen Z's anime consumption habits and how those factors impact their social interactions.